Cumulative mortality of Aedes aegypti larvae treated with compounds - Torres, Sandra Maria; Cruz, Nadine Louise Nicolau da; Rolim, Vitor Pereira de Matos; Cavalcanti, Maria Inês de Assis; Alves, Leucio Câmara; Silva Júnior, Valdemiro Amaro da (Revista de Saúde Pública, 2014)
OBJECTIVE To evaluate the larvicidal activity of Azadirachta indica, Melaleuca alternifolia, carapa guianensis essential oils and fermented extract of Carica papaya against Aedes aegypti (Linnaeus, 1762) (Diptera: Culicidae). METHODS The larvicide test was performed in triplicate with 300 larvae for each experimental group using the third larval stage, which were exposed for 24h. The groups were: positive control with industrial larvicide (BTI) in concentrations of 0.37 ppm (PC1) and 0.06 ppm (PC2); treated with compounds of essential oils and fermented extract, 50.0% concentration (G1); treated with compounds of essential oils and fermented extract, 25.0% concentration (G2); treated with compounds of essential oils and fermented extract, 12.5% concentration (G3); and negative control group using water (NC1) and using dimethyl (NC2). The larvae were monitored every 60 min using direct visualization. RESULTS No mortality occurred in experimental groups NC1 and NC2 in the 24h exposure period, whereas there was 100% mortality in the PC1 and PC2 groups compared to NC1 and NC2. Mortality rates of 65.0%, 50.0% and 78.0% were observed in the groups G1, G2 and G3 respectively, compared with NC1 and NC2. CONCLUSIONS The association between three essential oils from Azadirachta indica, Melaleuca alternifolia, Carapa guianensis and fermented extract of Carica papaya was efficient at all concentrations. Therefore, it can be used in Aedes aegypti Liverpool third larvae stage control programs.